Pemanfaatan Platform Media Sosial Instagram dan Tiktok dalam Merumuskan Strategi Konten Visual Pada fitinline.com [The Use of Instagram and TikTok in Developing Visual Content Strategies for Fitinline.com] - Yudianto, Firman; Nisa, Dwi Nur Khafidatun; Yuliana, Leni; Meutia, Nur Shabrina (Indonesia Berdaya, 2026)
The rapid development of social media as a primary digital marketing channel requires companies to implement visual content strategies that are well-directed, consistent, and aligned with audience characteristics. Fitinline.com, an educational and e-commerce platform in the fashion and textile sector, faces several challenges, including low visual consistency, monotonous content formats, and suboptimal engagement on Instagram and TikTok. This internship program aimed to analyze digital content needs, formulate visual content strategies, and implement the distinctive features of both platforms to enhance engagement and strengthen brand identity.The methods employed included initial observation of social media conditions, content performance analysis, discussions with mentors, and the implementation of strategies based on brand guidelines, content pillars, and platform-specific characteristics. The results indicate that the systematic application of visual content strategies—through consistent typography, color schemes, layouts, storytelling, and the optimization of Instagram carousel features and TikTok short-form videos—successfully increased reach, interaction, and follower growth. Therefore, the visual content strategy developed during the internship period provides a more structured direction for digital content management and has the potential to strengthen Fitinline.com’s position as a credible fashion education platform on social media. Abstrak. Should Perkembangan media sosial sebagai kanal utama digital marketing menuntut perusahaan untuk memiliki strategi konten visual yang terarah, konsisten, dan relevan dengan karakter audiens. Fitinline.com sebagai platform edukasi dan e-commerce di bidang fashion dan tekstil menghadapi tantangan berupa rendahnya konsistensi visual, format konten yang monoton, serta engagement yang belum optimal pada platform Instagram dan TikTok. Kegiatan magang ini bertujuan untuk menganalisis kebutuhan konten digital, merumuskan strategi konten visual, serta mengimplementasikan pemanfaatan fitur khas kedua platform guna meningkatkan engagement dan penguatan identitas merek. Metode yang digunakan meliputi observasi kondisi awal media sosial, analisis performa konten, diskusi dengan mentor, serta implementasi strategi berbasis brand guideline, content pillar, dan karakteristik platform. Hasil kegiatan menunjukkan bahwa penerapan strategi konten visual yang sistematis melalui konsistensi tipografi, warna, layout, storytelling, serta optimalisasi fitur carousel Instagram dan video pendek TikTok mampu meningkatkan jangkauan, interaksi, dan pertumbuhan pengikut. Dengan demikian, strategi konten visual yang dirumuskan selama periode magang terbukti memberikan arah pengelolaan konten digital yang lebih terstruktur dan berpotensi memperkuat posisi Fitinline.com sebagai platform edukasi fashion yang kredibel di media sosial.